Psychoanalysis Ego Image by Freudian: Study of Psychology in the Main Character of the Tale of Hang Tuah - Tia Pratiwi; Sarwiji Suwandi; Nugraheni Eko Wardhani (Budapest International Research and Critics University, 2019)
The tale of Hang Tuah is one type of old literature. This folklore tells the story of the main character named Hang Tuah who became the commander of a kingdom in a Malay land called the kingdom of Malacca. The purpose of this study is to analyze the psychology of the main character of the tale of Hang Tuah based on Sigmund Freud's psychoanalytic theory. This study uses descriptive qualitative study by analyzing the contents contained in the tale of Hang Tuah by Bot GenootSchap. The data in this study are in the form of behavior carried out by the main character, and the psychology of the main character based on the actions taken. Data sources in this study are in the form of a book entitled the tale of Hang Tuah, supporting primary books, and relevant journals and research as well. The data analysis technique used in this study is content analysis. The results of this study can be concluded that Based on the analysis carried out on the tale of Hang Tuah story script, it can be concluded that the character, Hang Tuah, has a personality that is consistent with what is conveyed in Sigmund Freud's psychoanalytic theory, especially in the ego aspect.